The strategies preventing particle transportation into the inlets of nuclear power plants: Mechanisms of physical oceanography - Li, Jintao; Xu, Mengdi; Lin, Jianwei; Jiang, Yuwu (Frontiers in Marine Science, 2023)
The occurrence of aquatic organism aggregations near the inlet of nuclear power plant (NPP) has become an important issue around the globe, since the aggregated organisms can block the cooling system and threaten the operation safety of NPP. In this study we focus on the trajectory of aquatic organism, i.e., how these organism can be transported to the inlet of NPP by ocean physical processes related with currents and waves. The Changjiang NPP located at the west side of the Hainan Island in China experiences serious gulfweed blocking events occasionally in spring. In order to study the physical mechanism, with the use of a 3D numerical current-wave coupled model, the current and wave conditions near the NPP was simulated. Based on the model, several particle tracking simulations were run to evaluate the extent of the blocking occurred in the inlet of the NPP’s cooling system with different forcings introduced. Results showed that the windage effect and surface Stokes drift induced by waves were the main cause for the blocking events in the Changjiang NPP, with the former transporting surface particles from upstream and the latter transporting surrounding particles onshore into the NPP’s inlet. Further simulations revealed that bending of the inlet, changing offshore mouth to downstream mouth could prevent the blocking greatly, as the particle was seldom transported into the mouth by cross-shore transport processes like Stokes drift. We suggest such findings may provide reference value for the prevention strategies of the aquatic organism aggregation events occurred in other NPPs.